A 100-Year Review: Advances in goat milk research - Clark, Stephanie; Mora García, María Bárbara (Journal of dairy science, 2017)
In the century of research chronicled between 1917 and 2017, dairy goats have gone from simply serving as surrogates to cows to serving as transgenic carriers of human enzymes. Goat milk has been an important part of human nutrition for millennia, in part because of the greater similarity of goat milk to human milk, softer curd formation, higher proportion of small milk fat globules, and different allergenic properties compared with cow milk; however, key nutritional deficiencies limit its suitability for infants. Great attention has been given not only to protein differences between goat and cow milk, but also to fat and enzyme differences, and their effect on the physical and sensory properties of goat milk and milk products. Physiological differences between the species necessitate different techniques for analysis of somatic cell counts, which are naturally higher in goat milk. The high value of goat milk throughout the world has generated a need for a variety of techniques to detect adulteration of goat milk products with cow milk. Advances in all of these areas have been largely documented in the Journal of Dairy Science (JDS), and this review summarizes such advances.